2019
DOI: 10.1002/ejic.201900528
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Functionalized Organotin Trichlorides and Their Tin Sulfide Clusters

Abstract: We present a new synthesis of functionalized tin sulfide clusters via organotin trichlorides with boc-protected amino acids (R AAc SnCl 3 ). In this work we used non-polar (alanine, valine, leucine, phenylalanine and methionine), polar/neutral (serine and tyrosine) and basic (histidine) amino acids. We obtained single crystals from a Boc-protected valine derivative of the originally used organotin trichloride R 1 SnCl 3 [R 1 = [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…75 Reactions with bifunctional molecules cause intramolecular bridging of inorganic scaffolds by the organic substituents under formation of macrocyclic or cavitand-like molecules of the composition 56 Inspired by the biological activity of organotin compounds, a special emphasis was put on the attachment of biomolecules to organotin chalcogenide clusters in recent years, with the long-term goal of nding new enzyme inhibitors and cytostatic drugs. For this purpose, a wide range of amino acids and oligopeptides have successfully been attached either via reaction with amino acid hydrazides, 79,80 or via click chemistry. 81,82 Biological or medical use have not yet come into sight, but the groundwork for further extensions in this direction has been laid.…”
Section: Organotin Chalcogenide Clusters and Related Compoundsmentioning
confidence: 99%
“…75 Reactions with bifunctional molecules cause intramolecular bridging of inorganic scaffolds by the organic substituents under formation of macrocyclic or cavitand-like molecules of the composition 56 Inspired by the biological activity of organotin compounds, a special emphasis was put on the attachment of biomolecules to organotin chalcogenide clusters in recent years, with the long-term goal of nding new enzyme inhibitors and cytostatic drugs. For this purpose, a wide range of amino acids and oligopeptides have successfully been attached either via reaction with amino acid hydrazides, 79,80 or via click chemistry. 81,82 Biological or medical use have not yet come into sight, but the groundwork for further extensions in this direction has been laid.…”
Section: Organotin Chalcogenide Clusters and Related Compoundsmentioning
confidence: 99%
“…By exploitation of the carbonyl group or a hydrazone group formed from it, a synthesis strategy involving mild reaction conditions can be applied, so that molecules with different functionalities can be covalently linked to the inorganic core. In this way, organotin sulfides with attached biomolecules, chelating ligands for the trapping of metal ions, , and small organic and aromatic , ligands have been achieved. In addition, some compounds exhibiting distinct optical absorption and emission properties have been synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of metal-metal interaction in clusters have been developed and widely studied as some important research dealt with the synthesis and characterization of the anionic complexes (1)(2)(3)(4)(5). Some were studies of cluster with low valent metal such as Fe 2 (CO) 9 , showed that the Fe-Fe separation was short enough to imply a M-M bond (6)(7)(8)(9)(10)(11). The important development in the topological analysis, specifically, the atoms in molecules (AIM) theory which developed by Bader and his group, is to study both experimental and theoretical electron density distributions.…”
Section: Introductionmentioning
confidence: 99%